SOCIOLINGUISTIC ANALYSIS ON ORAL LANGUAGE VARIATION OF SELLERS AND PURCHASERS IN PASAR JOHAR SEMARANG - Megasari, Tety (LANTERN (Journal on English Language, Culture and Literature), 2013)
In PasarJohar Semarang, it is found a lot of sellers selling their goods or their services to domestics or even foreign purchasers, but especially society in Semarang. PasarJohar is a place for those who like shopping, especially for searching batik or other clothes. In this final project, the writer tries to conduct research with a different subject of research that is variety of language used by sellers and purchasers. It is expected to find out the characteristics of language used by some sellers and purchasers in PasarJohar Semarang.